Ramen – A Japanese National Dish with Chinese National Heritage - Kushner, Barak (Petits Propos Culinaires, 2013)
The article is a reworking, by the author, of the first chapter of Slurp! A Social and Culinary History of Ramen – Japan’s Favorite Noodle Soup which was published in 2012 by Brill. It provides a history of traditional ramen as well as its offshoot, instant noodles.